Long-Term Health Effects of Nuclear Tests: The Semipalatinsk Case - Karlygash Kuralbayeva; Cinzia Rienzo; Po Yin Wong; Gaby Guerrero-Serdan (Global Labor Organization (GLO), 2025)
Using the Semipalatinsk Test Site in Kazakhstan, where about 456 nuclear tests occurred between 1949 and 1989, this paper examines the long-term health and well-being impacts of sustained radiation exposure. Results show that nuclear exposure significantly increases the risk of chronic disease and anemia, reduces subjective health, and lowers life satisfaction, with higher exposure intensities amplifying these effects. Older cohorts who, since early age, have been exposed to atmospheric testing face the greatest risks. These findings highlight the multigenerational health impacts of repeated radiation exposure, offering critical insights for public and health policy.
Keywords: J24; H00; Q50; Q53; 330; Health; life satisfaction; nuclear tests explosions; environment